The effect of uniaxial crystal-field anisotropy on magnetic properties of the superexchange antiferromagnetic Ising model - Canova, L.; Jascur, M. (Condensed Matter Physics, 2006)
The generalized Fisher super-exchange antiferromagnetic model with uniaxial crystal-field anisotropy is exactly
investigated using an extended mapping technique. An exact relation between partition function of the
studied system and that of the standard zero-field spin-1/2 Ising model on the corresponding lattice is obtained
applying the decoration-iteration transformation. Consequently, exact results for all physical quantities
are derived for arbitrary spin values S of decorating atoms. Particular attention is paid to the investigation
of the effect of crystal-field anisotropy and external longitudinal magnetic field on magnetic properties of the
system under investigation. The most interesting numerical results for ground-state and finite-temperature
phase diagrams, thermal dependences of the sublattice magnetization and other thermodynamic quantities
are discussed